Improving the Quality of Public Services in Kadu Jaya Village, Curug Sub-District, Tangerang District - Muhammad Misbachul Kahfi; Muhammad Rosul Asmawi; Pri Utami (Peneliti.net, 2023)
The quality of public services is an effort to fulfill everything related to the needs of the community, both in the needs of administrative groups, needs in groups of goods and needs in groups of services. At this time, it is felt that public services in the village government are still unable to face the challenges of being a government organizer capable of providing good public services to the village community. The purpose of this study is to determine the quality of public services in Kadu Jaya Village and to find out the inhibiting factors in improving the quality of public services in Kadu Jaya Village, Curug District, Tangerang Regency.This research uses descriptive qualitative research methods. The reason the author chose this is that the author wants to explore the facts about the quality of public services in Kadu Jaya Village, Curug Subdistrict, Tangerang Regency and what are the inhibiting factors in the quality of public services in the village. The research results show that the quality of service in Kadu Jaya Village, Curug Subdistrict, Tangerang Regency can be said to be good, but there are several things that should be of concern, namely the level of employee discipline that needs to be improved, the delivery of policy information to the community which must be more evenly distributed and the certainty and clarity of service fees that must be conveyed openly to the community. Meanwhile, the factors that hamper the improvement of service quality in Kadu Jaya Village, Curug Subdistrict, Tangerang Regency are the lack of quantity and quality of service employees, low discipline of government officials, poor delivery of village policy information to the community and the lack of public curiosity about Kadu Jaya village government policies.